Utilization of Metarhizium as an insect biocontrol agent and a plant bioinoculant with special reference to Brazil - Mesquita, Emily; Hu, Shasha; Lima, Tais B.; Golo, Patricia Silva; Bidochka, Michael J. (Frontiers in Fungal Biology, 2023)
Brazil has a long history of using biological control and has the largest program in sugarcane agriculture to which a biocontrol program has been applied. This achievement is at least partly due to the utilization of the entomopathogenic fungus Metarhizium. This well-known fungal genus exhibits pathogenicity against a broad range of arthropod hosts and has been used globally as a biocontrol agent. This fungus is also a root symbiont, and in this capacity, it is a plant growth promoter. However, this feature (i.e., as a plant symbiont) has yet to be fully explored and implemented in Brazil, although the number of reports demonstrating Metarhizium’s utility as a plant bioinoculant is increasing. The Brazilian bioproduct industry targets agricultural pests, and is limited to two Metarhizium species represented by four fungal isolates as active ingredients. Entomopathogenic fungi have also been successful in controlling arthropods of public health concern, as shown in their control of mosquitoes, which are vectors of diseases. The isolation of new indigenous Metarhizium isolates from a variety of substrates such as soil, insects, and plants shows the wide genetic diversity within this fungal genus. In this review, we emphasize the significance of Metarhizium spp. for the biological control of insects in Brazil. We also suggest that the experience and success of biological control with fungi in Brazil is an important resource for developing integrated pest management and sustainable strategies for pest control worldwide. Moreover, the future implementation prospects of species of Metarhizium being used as bioinoculants and possible new advances in the utility of this fungus are discussed.